Machine Learning to Predict the 1-Year Mortality Rate After Acute Anterior Myocardial Infarction in Chinese Patients - Li Y; Jiang L; He J; Jia K; Peng Y; Chen M (Dove Medical Press, 2020)
Yi-ming Li,1,* Li-cheng Jiang,2,* Jing-jing He,1 Kai-yu Jia,1 Yong Peng,1 Mao Chen1 1Department of Cardiology, West China Hospital, Sichuan University, Chengdu, People’s Republic of China; 2Department of Cardiology, The First Affiliated Hospital, Chengdu Medical College, Chengdu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yong Peng; Mao ChenDepartment of Cardiology, West China Hospital, Sichuan University, 37 Guoxue Street, Chengdu 610041, People’s Republic of ChinaEmail pengyongcd@126.com; hmaochen@vip.sina.comAbstract: A formal risk assessment for identifying high-risk patients is essential in clinical practice and promoted in guidelines for the management of anterior acute myocardial infarction. In this study, we sought to evaluate the performance of different machine learning models in predicting the 1-year mortality rate of anterior ST-segment elevation myocardial infarction (STEMI) patients and to compare the utility of these models to the conventional Global Registry of Acute Coronary Events (GRACE) risk scores. We enrolled all of the patients aged >18 years with discharge diagnoses of anterior STEMI in the Western China Hospital, Sichuan University, from January 2011 to January 2017. A total of 1244 patients were included in this study. The mean patient age was 63.8±12.9 years, and the proportion of males was 78.4%. The majority (75.18%) received revascularization therapy. In the prediction of the 1-year mortality rate, the areas under the curve (AUCs) of the receiver operating characteristic curves (ROCs) of the six models ranged from 0.709 to 0.942. Among all models, XGBoost achieved the highest accuracy (92%), specificity (99%) and f1 score (0.72) for predictions with the full variable model. After feature selection, XGBoost still obtained the highest accuracy (93%), specificity (99%) and f1 score (0.73). In conclusion, machine learning algorithms can accurately predict the rate of death after a 1-year follow-up of anterior STEMI, especially the XGBoost model.Keywords: machine learning, prediction model, acute anterior myocardial infarction